1985
DOI: 10.1063/1.449815
|View full text |Cite
|
Sign up to set email alerts
|

Formation and dissociation of doubly ionized methane

Abstract: Translational energy spectra of H− ions arising from double charge transfer to 1.5–7.0 keV protons from methane have been recorded and interpreted as the single and double ionization spectra of CH4. The excited states of CH++4 are not resolved, but a large broad peak of 4 eV half-width is observed, starting at around 35 eV, with a long tail extending to 44 eV. The peak maximum is at 38.6 eV. Four dissociation reactions of CH2+4 have been observed using photoion–photoion coincidence techniques with Heii light. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…Formation of unstable dications, CH 2+ 4 , in photoionization of CH 4 has already been observed by Fournier et al 97 According to their measurements, the dication formed from 44 eV photon impact decays preferentially into (CH us to evaluate quantitatively the contribution from multiple ionization into the experimental cross sections. Knowing that half of the H + ions observed experimentally at 100 eV come from double ionization, we can roughly estimate the counting ionization cross section in methane by subtracting half of the recommended H + cross section from the recommended total (=gross) cross section,…”
Section: Semi-empirical Estimates and Counting Ionization Cross Sectionmentioning
confidence: 79%
“…Formation of unstable dications, CH 2+ 4 , in photoionization of CH 4 has already been observed by Fournier et al 97 According to their measurements, the dication formed from 44 eV photon impact decays preferentially into (CH us to evaluate quantitatively the contribution from multiple ionization into the experimental cross sections. Knowing that half of the H + ions observed experimentally at 100 eV come from double ionization, we can roughly estimate the counting ionization cross section in methane by subtracting half of the recommended H + cross section from the recommended total (=gross) cross section,…”
Section: Semi-empirical Estimates and Counting Ionization Cross Sectionmentioning
confidence: 79%
“…However, the kinetic energy of 3.7 eV for protons emitted after double-ionization states turns out to be much smaller than the result in Ref. [15]. Gluch et al measured the KED of protons from the dissociation of methane in electron impact reactions [9]; they found the first two groups in the proton KED as Latimer et al observed.…”
Section: Introductionmentioning
confidence: 84%
“…As DCT is a charge-transfer reaction due to collision with a medium-energy ion beam, it is believed to result in a truly vertical transition to the dication [16][17][18]. On the other hand, an influence of the nuclear dynamics in the core-ionized state on Auger spectra is well known.…”
Section: Discussionmentioning
confidence: 99%
“…The dicationic states of this molecule, in particular the ground state, have attracted considerable interest. Methods for their investigation include Auger decay [13,14], charge stripping spectroscopy (see the critical review in [15]), double charge transfer [16][17][18], photoelectron-ion-ion coincidence spectroscopy [19], photoelectron-photoelectron coincidence spectroscopy [20], coincidence spectroscopy of Auger electrons and ions [21][22][23], and quantum chemical calculations [15,[23][24][25][26]. The four lowest dicationic states actually possess a potential-energy surface with a local minimum [23], i.e., CH 2+ 4 can be metastable.…”
Section: Introductionmentioning
confidence: 99%